Learning about common and private values in oligopoly. (March 2015) - Bernhardt, Dan; Taub, Bart
<x xml:space="preserve">Abstract</x> We characterize a duopoly buffeted by demand and cost shocks. Firms learn about shocks from common observation, private observation, and noisy price signals. Firms internalize how outputs affect a rival's signal, and hence output. We distinguish how the nature of information —public versus private—and of what firms learn about—common versus private values—affect equilibrium outcomes. Firm outputs weigh private information about private values by more than common values. Thus, prices contain more information about private‐value shocks.